An Opportunity for Me? The Role of Resources in Opportunity Evaluation Decisions - Haynie, J. Michael; Shepherd, Dean A.; McMullen, Jeffery S. (Journal of Management Studies, 2009)
abstractWe apply the prescriptions of the resource‐based perspective to develop a model of entrepreneurial opportunity evaluation. We propose that opportunity evaluation decision policies are constructed as future‐oriented, cognitive representations of ‘what will be’, assuming one were to exploit the opportunity under evaluation. These cognitive representations incorporate both (1) an evaluation of the existing resource endowments (already under the control of the venture), which may be employed to exploit the opportunity under evaluation, and at the same time (2) an assessment of the future, wealth generating resources that must be marshalled (and subsequently under the control of the venture) in order to exploit the opportunity under evaluation. We empirically test this model using conjoint analysis and hierarchical linear modelling techniques to decompose more than 2300 opportunity evaluation decisions nested in a sample of 73 entrepreneurs. Our findings suggest that entrepreneurs are attracted to opportunities that are complementary to their existing knowledge resources; however, we also identify a set of opportunity‐specific and firm‐specific conditions that encourage entrepreneurs to pursue the acquisition and control of resources that are inconsistent with the existing, knowledge‐based resources of the venture. We identify these conditions and discuss implications for theory, practice, and future research.